Adoption of Scientific Poultry Farming Practices by the Farmers in Ajmer District of Rajasthan (Indian Journal of Extension Education, 2012)
Poultry farming has proved that it can ensure economic and social rehabilitation of weaker sections of the society. The knowledge and adoption of poultry farming are inter linked. It was observed that all the three categories of registered farmers adopted the recommended poultry farming practices at higher extent in comparison to unregistered poultry farmers. Although, a highly significant difference between different categories i.e. between the big and medium, big and small, medium and small of registered and unregistered poultry farmers was observed about extent of adoption of the recommended poultry farming practices. The study concludes that registered poultry farmers may have obtained training and exposure which enhanced the knowledge and ultimately had to encourage the farmers for more adoption of recommended poultry farming practices.